Análise da maturidade do modelo de um escritório de gerenciamento de projetos: estudo de caso de uma instituição científica e tecnológica - Fontes, Fernanda Gomes (2013)
This dissertation aims to establish a relationship between the level of maturity of an organization and its adherence to the guidelines established in the PMBOK® Guide through the analysis of an existing project management model in a Scientific and Technological Institution of federal public service.A self-assessment questionnaire of applicable functions of the Project Management Office (PMO) was conducted to generate results concerning the needs, for both existing and perceived, maturity level of organizational functions.With this information, important conclusions were drawn about the perceived intention of improvement in the process of maturity assesments and, consequently, were used to generate a plan of action to raise the level of organizational maturity in project management